Penerapan Model Pembelajaran Drill and Practice Menggunakan Media Focusky untuk Mengetahui Hasil Belajar TIK pada Siswa Kelas VIII SMPN Karangkancana Kabupaten Kuningan - Sukardi, Dadi; Zakaria, Yoyo (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the application of the drill and practice learning model using Focusky media to determine the ICT learning outcomes in grade VIII students of SMPN 1 Karangkancana, Kuningan Regency. The research method applied in this study is quantitative by applying a drill and practice learning model in grade VIII students of Karangkancana Junior High School. The results of the study show that the application of scientific research methods that use numbers to measure and analyze data. The hypothesis test was carried out by system experts, namely using the SPSS V26 application and produced a 100% result which was included in the "Very Feasible" category. The results of student responses to the results of the application of the drill and practice learning model using Focusky media obtained from hypothesis tests were also strengthened by the results of starting the pretest mean. 53.66, while the mean postest is 81.33 so that the difference between the pretest and the posttest is 27.67 The hypothesis results can be said to be significant and feasible, there is a significant increase after applying the drill and practice learning model